Pengaruh Model Pembelajaran Conceptual Understanding Procedures (CUPs) Terhadap Kemampuan Kolaborasi Higher Order Thinking Skills (HOTS) - Alfath, Haliza Auliana; Maritasari, Donna Boedi; Zohrani (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: This study aims to examine the effect of the conceptual understanding procedures (CUPs) learning model on the collaborative ability of higher order thinking skills (HOTS) in fourth-grade students of SDN 2 Masbagik Timur. This study uses a quantitative method with an experimental type with a true experimental design with a posttest-only control design. The subjects of the study were 48 fourth-grade students of SDN 2 Masbagik Timur, who were divided into 24 students in the experimental class (IV A) and 24 students in the control class (IV B). Data collection techniques include observation and tests. The research instrument has been tested for validity and reliability, the validity test in this study used the Pearson product moment correlation test where 15 valid questions out of 15 questions tested were considered valid with a significance level of 5%, while the reliability test used the KR 21 formula using Excel with a Cronbach's alpha value of 0.747544 which means the Cronbach's alpha value is greater than 0.6 and can be said to be reliable. The results of the study showed that the average posttest value of HOTS collaboration ability in the experimental class (84.91) was higher than the control class (78.37). The hypothesis test showed a significance value (Sig. 2-tailed) of 0.002, which is smaller than 0.05, so the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The normality test showed that the significance value Asymp. Sig. (2-tailed) of 0.176 was greater than 0.05. So, according to the basis for decision making in the normality test, it can be concluded that the data is normally distributed, while the results of the homogeneity test, the Sig. Levene's test for equality of variances is 0.262 0.05, which means that the data variance between group A and group B is homogeneous or the same. Thus, it can be concluded that the CUPs learning model has a positive and significant influence on improving the HOTS collaboration ability of fourth-grade students of SDN 2 Masbagik Timur. This learning is proven to be more active, creative, and fun, and motivates students to collaborate and take responsibility in the learning process. Abstrak: Penelitian ini bertujuan untuk menguji pengaruh model pembelajaran conceptual understanding procedures (CUPs) terhadap kemampuan kolaborasi higher order thinking skills (HOTS) pada peserta didik kelas IV SDN 2 Masbagik Timur. Penelitian ini menggunakan metode kuantitatif dengan jenis eksperimen dengan desain true experimental design dengan bentuk posttest-only control design. Subjek penelitian adalah 48 peserta didik kelas IV SDN 2 Masbagik Timur, yang dibagi menjadi 24 peserta didik di kelas eksperimen (IV A) dan 24 peserta didik di kelas kontrol (IV B). Teknik pengumpulan data meliputi observasi dan tes. Instrumen penelitian telah diuji validitas dan reliabilitasnya, uji validitas pada penelitian ini menggunakan uji korelasi pearson product moment yang dimana 15 butir soal valid dari 15 butir soal yang diuji terbilang valid dengan taraf signifikan 5%, sedangkan uji reliabilitas menggunakan rumus KR 21 dengan menggunakan bantuan excel dengan nilai Cronbach’s alpha sebesar 0,747544  yang artinya nilai Cronbach’s alpha lebih besar dari 0,6 dan dapat dikatan reliabel. Hasil penelitian menunjukkan bahwa nilai rata-rata posttest kemampuan kolaborasi HOTS pada kelas eksperimen (84,91) lebih tinggi dibandingkan kelas kontrol (78,37). Uji hipotesis menunjukkan nilai signifikansi (Sig. 2-tailed) sebesar 0,002, yang lebih kecil dari 0,05, sehingga hipotesis nol (H0) ditolak dan hipotesis alternatif (Ha) diterima. Uji normalitas menunjukkan bahwa nilai signifikansinya Asymp. Sig. (2-tailed) sebesar 0,176 lebih besar dari 0,05. Maka sesuai dengan dasar pengambilan keputusan dalam uji normalitas, dapat disimpulkan bahwa data berdistribusi normal, adapun hasil uji homogenitasnya nilai Sig. Levene’s test for equality variances adalah 0,2620,05  maka dapat diartikan bahwa varians data antara kelompok A dan kelompok B adalah homogen atau sama. Dengan demikian, dapat disimpulkan bahwa model pembelajaran CUPs memiliki pengaruh positif dan signifikan terhadap peningkatan kemampuan kolaborasi HOTS peserta didik kelas IV SDN 2 Masbagik Timur. Pembelajaran ini terbukti lebih aktif, kreatif, dan menyenangkan, serta memotivasi peserta didik untuk berkolaborasi dan bertanggung jawab dalam proses belajar.